NMDA receptors elicit flux-independent intracellular Ca2+ signals via metabotropic glutamate receptors and flux-dependent nitric oxide release in human brain microvascular endothelial cells. (November 2021) - Negri, Sharon; Faris, Pawan; Maniezzi, Claudia; Pellavio, Giorgia; Spaiardi, Paolo; Botta, Laura; Laforenza, Umberto; Biella, Gerardo; Moccia, Dr. Francesco
Highlights: NMDA causes an increase in [Ca 2+ ]i in the human brain microvascular endothelial cell line, hCMEC/D3. NMDARs increase the [Ca 2+ ]i in a flux-independent manner via group 1 mGluRs. NMDARs may also induce NO release by signaling in a flux-dependent manner. Endothelial NMDA receptors exploit both canonical and non-canonical signaling modes. Abstract: The excitatory neurotransmitter glutamate gates post-synaptic N-methyl-d -aspartate (NMDA) receptors (NMDARs) to mediate extracellular Ca 2+ entry and stimulate neuronal nitric oxide (NO) synthase to release NO and trigger neurovascular coupling (NVC). Neuronal and glial NMDARs may also operate in a flux-independent manner, although it is unclear whether their non-ionotropic mode of action is involved in NVC. Recently, endothelial NMDARs were found to trigger Ca 2+ -dependent NO production and induce NVC, but the underlying mode of signaling remains elusive. Herein, we report that GluN1 protein, as well as GluN2C and GluN3B transcripts and proteins, were expressed and that NMDA did not elicit inward currents, but induced a dose-dependent increase in intracellular Ca 2+ concentration ([Ca 2+ ]i ) in the human brain microvascular endothelial cell line, hCMEC/D3. A multidisciplinary approach, including live cell imaging, whole-cell patch-clamp recordings, pharmacological manipulation and gene targeting, revealed that NMDARs increase the [Ca 2+ ]i in a flux-independent manner in hCMEC/D3 cells. The Ca 2+ response to NMDA was triggered by endogenous Ca 2+ release from the endoplasmic reticulum and the lysosomal Ca 2+ stores and sustained by store-operated Ca 2+ entry. Unexpectedly, pharmacological and genetic blockade of mGluR1 and mGluR5 dramatically impaired NMDARs-mediated Ca 2+ signals. These findings indicate that NMDARs may increase the endothelial [Ca 2+ ]i in a flux-independent manner via group 1 mGluRs. However, imaging of DAF-FM fluorescence revealed that NMDARs may also induce Ca 2+ -dependent NO release by signaling in a flux-dependent manner. These findings, therefore, shed novel light on the mechanisms whereby brain microvascular endothelium decodes glutamatergic signaling and regulates NVC. Graphical abstract: Image, graphical abstract